The Role of Green Accounting in Advancing Corporate Climate Transition Strategies - Maimuna Maimuna; Jayana Salesti; Hanafi Siregar; Ravika Permata Hati (Journal of Economics and Management Scienties, 2026)
This study examines how green accounting supports corporate climate transition strategies by analyzing documented evidence from academic literature, regulatory frameworks, and corporate sustainability reports. Using a qualitative descriptive approach, the research applies thematic analysis to identify recurring patterns in the use of environmental metrics, climate risk assessments, and reporting mechanisms. The findings show that companies increasingly employ structured indicators such as carbon emissions, energy intensity, and resource efficiency to establish transition baselines and evaluate environmental performance. Environmental accounting data also enable firms to assess climate related risks, allocate resources for low carbon investments, and integrate sustainability considerations into strategic planning. The study further reveals that transparent reporting practices enhance managerial accountability and strengthen stakeholder trust in transition progress. Overall, the results indicate that green accounting provides measurable information that improves organizational readiness, supports long-term decision making, and facilitates the development of coherent climate transition pathways.